(دور مجلس الدولة المصري في في حماية حرية العقيدة، وممارسة الشعائر الدينية (بناء الكنائس - وإدارتها نموذجا - أحمد رمضان, شعبان; سيد محمود, أحمد (University of Eloued جامعة الوادي, 2018)
The Egyptian reality says that the order to build or demolish the churches in Egypt was not according to the reconciliation that took place at the time of the conquest between Amr ibn al-'Aas and the Copts, but it depends on the policy of the ruler and the father or the mother. This explains the contradictions in the decisions of the governors in this regard. , Some of which prevent. In Egypt, there are no detailed laws concerning the building of churches until the date of the promulgation of Law No. 80 of 2016 regarding the organization of the work of building and repairing churches and their accessories, and the appropriation of the ruler in Egypt with the authority to issue the building permits of churches is the legacy of the rulers in Egypt since the Islamic conquest. Which has always been characterized by the generality, the foot, the steadfastness and the binding - approved by the Hamayouni line and did not create it - remained in existence despite the change and amendment of the constitutions and the systems of government in Egypt, which it has always called traditions or rules or what has been done. from US The President of the Republic of Egypt has the power to issue church building permits in accordance with the provisions of the Hamayouni line and the rules of the Ministry of Interior dictated by considerations of security and does not conflict with the freedom of belief, the practice of religious rites and does not violate the Constitution. Non-Muslim houses of worship There is no problem for any party because non-Muslim religious communities enjoy full independence in the administration of their religious affairs since the Islamic conquest of Egypt until the present day. The Ifta and the Council of State have established that the churches are the presidential institutions Religious, ie, the Patriarchate, and this makes the religious presidency alone the right to financial and administrative supervision over the Church with its jurisdiction over the affairs of the religious community and not to the authorities or any other authority any supervision of the Church in this regard as well as the recognition of non-Muslim religious communities recognized by the internal authority Public facilities have the characteristics of administrative persons, and their governing bodies and supervisory bodies have the same legal status.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: مجلس الدولة، الشعائر الدينية، حرية العقيدة، مصر